Au nanoparticle in situ decorated RGO nanocomposites for highly sensitive electrochemical genosensors. Issue 5 (9th January 2019) - Ingrosso, Chiara; Corricelli, Michela; Bettazzi, Francesca; Konstantinidou, Evgenia; Bianco, Giuseppe V.; Depalo, Nicoletta; Striccoli, Marinella; Agostiano, Angela; Curri, M. Lucia; Palchetti, Ilaria
Abstract : A novel hybrid nanocomposite formed by RGO flakes, surface functionalized by 1-pyrene carboxylic acid (PCA), densely and uniformly in situ decorated by Au NPs, is reported, for miRNA detection. Abstract : A novel hybrid nanocomposite formed by RGO flakes, surface functionalized by 1-pyrene carboxylic acid (PCA), densely and uniformly in situ decorated by Au NPs, that are concomitantly coordinated by the PCA carboxylic group, and by an aromatic thiol used as the reducing agent in the synthesis, both ensuring, at the same time, a stable non-covalent NPs anchorage to the RGO flakes, and an efficient interparticle electron coupling along the NP network onto the RGO, is reported. The obtained solution processable hybrid material is used to modify Screen-Printed Carbon Electrodes (SPCEs). The hybrid modified SPCEs, functionalized with a thiolated DNA capture probe, are tested in a streptavidin–alkaline-phosphatase catalyzed assay, for the detection of the biotinylated miRNA-221, and for its determination in spiked human blood serum samples. The proposed genosensor demonstrates a high sensitivity (LOD of 0.7 pM), attesting for a performance comparable with the most effective reported sensors. The enhanced sensitivity is explained in terms of the very fast heterogeneous electron transfer kinetics, the concomitant decrease of the electron transfer resistance at the electrode/electrolyte interface, the high electroactivity and the high surface area of the nanostructured hybrid modified SPCEs that provide a convenient platform for nucleic acid biosensing.